Characterizing nano-scale electrocatalysis during partial oxidation of methane - Lee, Daehee; Kim, Dongha; Kim, Joosun; Moon, Jooho (NATURE PUBLISHING GROUP, 2014)
Electrochemical analysis allows in situ characterization of solid oxide electrochemical cells (SOCs) under operating conditions. However, the SOCs that have been analyzed in this way have ill-defined or uncommon microstructures in terms of porosity and tortuosity. Therefore, the nano-scale characterization of SOCs with respect to three-phase boundaries has been hindered. Weintroduce novel in situ electrochemical analysis for SOCs that uses combined solid electrolyte potentiometry (SEP) and impedance measurements. This method is employed to investigate the oscillatory behavior of a porous Ni-yttria-stabilized zirconia (YSZ) anode during the partial oxidation of methane under ambient pressure at 800 degrees C. The cyclic oxidation and reduction of nickel induces the oscillatory behavior in the impedance and electrode potential. The in situ characterization of the nickel surface suggests that the oxidation of the nickel occurs predominantly at the two-phase boundaries, whereas the nickel at the three-phase boundaries remains in the metallic state during the cyclic redox reaction.
Keywords: OSCILLATORY BEHAVIOR; IN-SITU; CO OXIDATION; NI; TEMPERATURE; CATALYSIS; IMPEDANCE; STATE; ANODE; PD